2017
DOI: 10.1097/md.0000000000008182
|View full text |Cite
|
Sign up to set email alerts
|

Association between folate intake and risk of head and neck squamous cell carcinoma

Abstract: The results of published studies about the relationships between folate intake and risk of head and neck squamous cell carcinoma (HNSCC) remained inconsistent. Hence, a comprehensive and dose–response meta-analysis was performed to clarify the association between folate intake and HNSCC risk.The electric searches of Pubmed, Medline, and EMBASE databases were performed to identify the studies examining the relationship between folate intake and HNSCC risk on April 5, 2017. According to the inclusion criteria, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Inadequate folate intake or deficiency, as measured by serum levels, may increase risk for cancer, including cancers of the head and neck [ 18 ], oral cavity and pharynx [ 19 ], esophagus [ 21 ], pancreatic [ 21 , 22 ], bladder [ 25 ], and cervix. Low intake combined with high alcohol intake may also increase the risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inadequate folate intake or deficiency, as measured by serum levels, may increase risk for cancer, including cancers of the head and neck [ 18 ], oral cavity and pharynx [ 19 ], esophagus [ 21 ], pancreatic [ 21 , 22 ], bladder [ 25 ], and cervix. Low intake combined with high alcohol intake may also increase the risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“… NS Tio [ 52 ] 36 studies. Breast Dietary folate NS: once adjusted 608,265 sample size, 34,602 cases Total folate intake NS Menopausal status NS once adjusted Hormone status NS Study design S: retrospective study design showed decreased risk of postmenopausal breast cancer Fan C [ 18 ] 4,090/10,902 9 case-control studies: 7 dietary folate with FFQ; 2 studies serum folate concentration; 4 studies dose-response analysis Head and neck Folate intake S: decreased risk comparing highest to lowest folate intake Dose-response S: every 100 mcg/day increase in folate intake associated with 4.3% decreased risk Galeone C [ 19 ] 5,127/13,249 Pooled analysis of individual-level data from 10 case-control studies Oral cavity and pharyngeal (OPC) Total folate intake S: Reduced risk for highest compared lowest quintile total folate intake and overall OPC risk S: decreased risk for oral cavity Alcohol S: increased risk for heavy drinkers with low folate intake compared to low alcohol intake with higher folate intake Smoking S: increased risk for smoking Zhao Y [ 20 ] 19 studies Esophageal Dietary folate intake S: decreased risk with highest folate intake compared to lowest intake 14 case-control 1 cohort dietary folate intake 6 case-control 1 cohort for dose-response Dose-response S: 100 mcg/day increment in dietary folate intake reduced risk by 12% Tio M [ 21 ] 9 case-control 2574/9254 for any histological type of esophageal cancer. Esophageal, gastric, pancreatic Dietary folate S: dietary folate associated with decreased risk of esophageal and pancreatic cancer NS: gastric cancer 8 studies (5 prospective, 3 retrospective) 2209/295,526 for pancreatic cancer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In aktuellen Studien inklusive Metaanalysen zeigte sich eine protektive Wirkung für die Entwicklung von Kopf-Hals-Tumoren [9,10].…”
Section: Hno-tumorenunclassified